Influence of Motivation, HR Development and Management Support for Work Productivity at the Lebak Regency Transportation Service - Indah Lestari; Siti Iin Inayah; Muhi Mukti (Journal of Economy, Accounting and Management Science (JEAMS), 2024)
The aim of this research is to analyze the influence of Motivation, HR Development and Management Support both partially and simultaneously on Work Productivity at the Lebak Regency Transportation Service. This type of research uses quantitative methods with survey research. The population of this research is 154 employees at the Department of Transportation (DISHUB) Lebak Regency, Rangkasbitung, Banten. The sampling technique used was a random sampling technique using the Slovin formula, namely 61 research samples used in this research. Data analysis techniques using multiple linear regression were processed using the SPSS V.20 analysis tool. It was concluded in this research that motivation, human resource development, and management support partially or simultaneously had a positive and significant effect on the work productivity of Lebak Regency Transportation Service Employees, this shows that motivation plays a role in supporting work productivity.